Coordinate Cytokine Gene Expression In Vivo following Induction of Tuberculous Pleurisy in Guinea Pigs - Allen, Shannon Sedberry (American Society for Microbiology, 2003)
Tuberculous pleurisy is a severe inflammatory response induced by Mycobacterium tuberculosis organisms that have escaped from lung granulomata into the pleural space during pulmonary infection. We have used the guinea pig model of tuberculous pleurisy to examine several aspects of the immune response to this antigen-specific inflammatory event. Pleurisy was induced by injection of heat-killed M. tuberculosis H37Rv directly into the pleural space of guinea pigs previously vaccinated with M. bovis BCG. Four animals were euthanized each day over a period of 9 days. Fluid in the pleural cavity was analyzed for transforming growth factor β1 (TGF-β1) and total interferon (IFN) protein levels. In addition, RNA was obtained from pleural cells and examined for TGF-β1, tumor necrosis factor alpha (TNF-α), IFN-γ, and interleukin-8 (IL-8) expression by real-time PCR. Finally, pleural cells were examined for the ability to proliferate in response to concanavalin A and purified protein derivative (PPD) in vitro. In the pleural fluid, TGF-β1 protein concentrations increased over the course of the inflammatory response while IFN protein levels were not significantly altered. Expression of TGF-β1 mRNA peaked on days 3 and 4, and IFN-γ mRNA expression peaked on day 3 and then returned to background levels. TNF-α mRNA expression was highest on days 2 to 4, and IL-8 mRNA levels remained elevated between days 2 and 5, peaking on day 3 before returning to background levels. PPD-induced proliferative responses were evident by day 3 and remained present throughout the study. Analysis of cytokine expression during tuberculous pleurisy may lead to a better understanding of the self-healing nature of this manifestation of tuberculosis.